Identification of more productive, resilient and farmer-preferred chicken breeds for Ethiopian, Tanzanian and Nigerian smallholder farmers - CGIAR Research Program on Livestock (2019)
The innovation process involved on-farm testing of 12 chicken strains with 6,348 households living in diverse ago-ecologies of the three countries. Data were collected on traits and, together with a farmer trait preference study, used to develop evidence-based recommendations on the best chicken strains to be promoted in each country.